2007
DOI: 10.1152/jn.00251.2006
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic Vesicle Distribution and Release at Rat Diaphragm Neuromuscular Junctions

Abstract: Rowley KL, Mantilla CB, Ermilov LG, Sieck GC. Synaptic vesicle distribution and release at rat diaphragm neuromuscular junctions. J Neurophysiol 98: 478 -487, 2007. First published May 9, 2007 doi:10.1152/jn.00251.2006. Synaptic vesicle release at the neuromuscular junction (NMJ) is highly reliable and is vital to the success of synaptic transmission. We examined synaptic vesicle number, distribution, and release at individual type-identified rat diaphragm NMJ. Three-dimensional reconstructions of electron mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
74
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(82 citation statements)
references
References 42 publications
8
74
0
Order By: Relevance
“…Previous studies using electron microscopy to examine the distribution of synaptic vesicles in mammalian neuromuscular terminals have demonstrated that although vesicles are primarily clustered at active zones, they are also present throughout the terminal (Rowley et al, 2007). Consistent with this, we found that the addition of NH 4 Cl to reveal the total intracellular vesicle pool led to fluorescence increases over the entire presynaptic terminal.…”
Section: Discussionsupporting
confidence: 88%
“…Previous studies using electron microscopy to examine the distribution of synaptic vesicles in mammalian neuromuscular terminals have demonstrated that although vesicles are primarily clustered at active zones, they are also present throughout the terminal (Rowley et al, 2007). Consistent with this, we found that the addition of NH 4 Cl to reveal the total intracellular vesicle pool led to fluorescence increases over the entire presynaptic terminal.…”
Section: Discussionsupporting
confidence: 88%
“…Whether such differences might influence the presently reported effects of adenosine upon aging, needs to be explored at the light of the results obtained by Rowley et al (2007) and Ermilov et al (2007). However, in a previous work (see Ginsborg and Hirst, 1972) the initial quantal content of EPPs (either being low, in experiments where muscle contractions were paralyzed by high magnesium, or high in the experiments where muscle contractions were paralyzed by tubocurarine) did not influence the inhibitory effects of adenosine at the rat diaphragm neuromuscular junction.…”
Section: Discussionmentioning
confidence: 88%
“…Neuromuscular junctions differ in quantal content, safety factor, and adaptation to repetitive activation (see Ermilov et al, 2007;Rowley et al, 2007). Whether such differences might influence the presently reported effects of adenosine upon aging, needs to be explored at the light of the results obtained by Rowley et al (2007) and Ermilov et al (2007).…”
Section: Discussionmentioning
confidence: 99%
“…Neuromuscular junctions at fibers expressing MHC 2X and/or MHC 2B are larger and more complex than those at fibers expressing MHC Slow or MHC 2A isoforms (74). Synaptic vesicle density at active zones is lower in axon terminals at fibers expressing MHC 2X and/or MHX 2B isoforms than at those expressing MHC Slow or MHC 2A isoforms (66,79). In addition, mitochondria, rough endoplasmic reticulum, free polysomes, and nuclei are frequently interposed between postsynaptic specializations and myofibrils at fibers expressing MHC 2X and/or MHX 2B isoforms, not at fibers expressing MHC Slow or MHC 2A isoforms.…”
Section: Postnatal Development Of Diaphragm Muscle Motor Unitsmentioning
confidence: 93%
“…The safety factor for neuromuscular transmission (defined as the ratio of the excitatory postsynaptic potential amplitude to activation threshold of a muscle fiber) varies across fiber types, being larger for type IIb DIAm fibers than for type I or IIa fibers (25). With repeated activation, the amplitude of excitatory postsynaptic potentials declines to a greater extent at terminals of type I or IIa fibers than at type IIb fibers (79). Taken together, these findings suggest that the probability of synaptic vesicle release is reduced at type I or IIa fibers, which may serve to limit the depletion of synaptic vesicles from these terminals during repeated activation.…”
Section: Postnatal Development Of Diaphragm Muscle Motor Unitsmentioning
confidence: 99%